Rapid synthesis of nanocrystalline YAG via microwave-assisted solvothermal process - Prabhu Ramanujam; Vaidhy Vaidhyanathan; J.G.P. Binner; Shaghayegh Ghanizadeh; Zhaoxia Zhou; Chris Spacie (2018)
A rapid synthesis procedure for the preparation of nanocrystalline yttrium aluminium garnet (nYAG) particles has been developed, for the first time, using the combination of subcritical conditions and microwave irradiation. It is believed that the use of butanediol delayed the onset of pressure rise due to its low partial pressure, while the microwaves facilitated a selective crystallization of nanocrystalline YAG particles in the solvent medium. This methodology was found to encourage rapid bulk nucleation with minimal particle growth or agglomeration of nYAG particles. The resultant powder characteristics, examined using XRD and TEM analyses, revealed that a narrow window of pressure and temperature conditions needed to be maintained to achieve spherical particles in the size range 60‐80 nm without any intermediate phases being formed. The STEM/EDX and FTIR results obtained suggested that the nucleated YAG particles were masked by carbon clouds until they were completely crystallized into single phase YAG particles; this allowed them to be dispersed in water with little agglomeration.